2006
DOI: 10.1177/0040517507069122
|View full text |Cite
|
Sign up to set email alerts
|

A Multicriteria Decision Aid Approach on Navel Selection Problem for Rotor Spinning

Abstract: In studies about optimization of rotor spinning machine parameters, generally classical statistical methods have been used; the priorities and preferences of the yarn producer about yarn properties to get the desired end product characteristics have not been taken into consideration. However, machine part selection from possible alternatives with different properties and performance levels about yarn quality is a difficult task and inherently a multicriteria decision-making problem. In this study, it is proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…But it is very difficult to decide in the scenario of a textile manufacturing process owing to the complicated application of a wide range of dependent and independent parameter variables in a very long chain of the textile processes [1]. Meanwhile, the optimization of a textile manufacturing process in terms of scenario solution always involves the consideration of multiple objectives as the performance of a textile manufacturing process generally is governed by a few conflicting criteria with different significance [2]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…But it is very difficult to decide in the scenario of a textile manufacturing process owing to the complicated application of a wide range of dependent and independent parameter variables in a very long chain of the textile processes [1]. Meanwhile, the optimization of a textile manufacturing process in terms of scenario solution always involves the consideration of multiple objectives as the performance of a textile manufacturing process generally is governed by a few conflicting criteria with different significance [2]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Yarns drawn from the rotor groove make a 90 0 turn inside the nozzle. The rotation of the yarn around the inner walls of the nozzle creates additional false twists on the yarn between the rotor groove and yarn draw-off [2,3]. Furthermore, false twist insertion is a function of the friction between the yarn surface and extractive nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…Javadiyan et al [8] worked on seven different nylon/cotton blend ratios and reported that by increasing the nylon fiber blend ratio, the yarn elongation, abrasion resistance, tensile work of rupture, and hairiness significantly increase, whereas yarn tensile modulus decrease. Navels differ in their material, forms, number of grooves, existence of fluted inserts, length of ceramic parts, and grooves [9]. Smooth navels often give better yarn characteristics; the yarn is more resistant to rubbing and has good heat conductivity and generally less false twist; grooved navels can operate at lower twist levels; the running performance is better because of the greater false twist effect but hairiness does increase; ceramic navels with 4-6 grooves have proved advantageous in the spinning of blended yarns and fibers that are not strongly sensitive to heat [10].…”
Section: Introductionmentioning
confidence: 99%